Trajetos do envelhecimento: perspetivas teóricas e empíricas - Fernanda Daniel (Investigação, 2019)
Starting from different theoretical-conceptual paths, the book describes current investigations carried out in Portugal related to the aging process. With the participation of authors from three areas of social sciences (psychology, sociology, and social work), the book contributes to an eclectic, stimulating, pedagogic, and comprehensive reading on topics that are relevant to students of gerontology. Cognitive and Dementia Deficit, Functionality and Aging, Personal Social Networks and Trajectories of Aging: An Age and Gender Perspective, Anxiety, Depression, Psychosis, Sleep in the Elderly, Mindfulness and Compassion in Older People, Spirituality and Aging, Optimism and Hope are the addressed thematic and assumed as titles of the ten chapters that compose the work. By integrating and reflecting what is the state of art, the work will certainly be useful to all those interested in the health and well-being of the older people.